(untitled) (Praxis Educativa, 2018)
This text is a teaching narration about the theoretical and experimental exercise of the project “Dictionary of words and phrases from the Santa Fe coast”, which was developed by the subject Language and Literature in a secondary school in Santa Rosa de Calchines (Garay department, Santa Fe). As the author suggests, thinking about the teaching practice within the ethical act, a class narrative writing was adopted (Bajtín, Bubnova). This project covers the study of concepts such as; identity (Hall), understood as a collective construction in relation to otherness, and dialect (Halliday, Zambrano Castro), understood as a regional variety which enables the self-recognition. The goals of this work are to make known the project and to debate on lessons and teaching narrations as a thinking strategy